Persepsi iklan Lifebuoy Pencegah Covid-19 di Kelurahan Tempel Rejo Rejang Lebong - Edo Wiranto; Robby Aditya Putra; Hariya Toni (Fakultas Ushuluddin, Adab dan Dakwah IAIN Kerinci, 2021)
This study aims to determine public perceptions of advertising to prevent the spread of the Covid-19 virus. To describe this perception, the researcher focused on several sub-categories, namely applications through the sense of sight and sense of hearing so as to produce people's perceptions of messages in advertisements. The research method in this study used a qualitative approach, namely descriptive analysis. The subjects in this study were 3 people. Data collection techniques through in-depth interviews, observation, documentation and internet searching. The results of the study illustrate that, the application of perception through the sense of sight is very positive, where people consider the visuals displayed in this advertisement to be very attractive so that people do not get bored seeing it. The application of perception through the sense of hearing is also very good, because the audio presentation displayed in this advertisement uses language that is easy to understand and is accompanied by music. The public's perception of this message as a whole is positive. The conclusion of this research is the public's perception is that this advertisement attracts people's attention and changes people's behavior to follow the contents of the message in the advertisement, namely steps to protect themselves from the spread of the Covid-19 virus.